Teacher's Responsibility in Islamic Education (Relevance of Hamka and Hasan Langgulung Thought) - Nurhadi Nurhadi; Muhammad Irhamuddin Harahap (LP2M STIT Palapa Nusantara, 2021)
Duties and responsibilities of teachers are not limited in society, even teachers included in this case are essentially strategic components that have an important role and responsibility in determining the progress of the nation's life and become the foundation of expectations of children's parents to make their children good children (anaks haleh) who know how to carry out their religious obligations and have a noble character (akhlak al-karimah). This study aims to determine; What are the Responsibilities of Teachers in Islamic Education according to Hasan Langgulung's Thought ?. What are the Responsibilities of Teachers in Islamic Education according to Buya Hamka's Thought ?. What is the relevance of Hasan Langgulung and Buya Hamka's thoughts on the Responsibilities of Teachers in Islamic Education ?. This research is a library research that uses various sources of literature as a source of research data. Primary data sources are the book Hamka Institution of Life and Budi and Hasan Langgulung Man and Education, An Analysis of Psychology, Philosophy and Education. While secondary data sources in research are books, articles, magazines, newspapers, or other sources, which are then drawn from these data. Based on the results of the processed data, it can be seen that the responsibilities of Teachers in Islamic Education according to Buya Hamka's thinking based on the explanation above, then the responsibility of educators namely educating: a). Faith Education; b). Moral education (morals); c). Physical education (physical and spiritual); d). Community social education; e). Intellectual education. While the Responsibility of Teachers in Islamic Education according to Hasan Langgulung's Thought covers at least 7 things, namely: a). Religious education which includes religious education, aqeedah and worship; b). Moral education (morals); c). Physical education which includes physical education and health; d). Psychological education consisting of psychiatric education and feelings; e). Community social education; f). Intellectual education. The relevance of the thoughts of Buya Hamka and Hasan Langgulung about the Responsibilities of Teachers in Islamic Education can be seen that Education basically revolves around science, charity, morals, and justice. All three are concepts that must be interconnected in the education process. Education for humans is not only to fulfill internal interests as dynamic creatures, but also external interests, namely the orderly and harmonious organization of human civilization.